2019
DOI: 10.5114/aoms.2019.84736
|View full text |Cite
|
Sign up to set email alerts
|

Risk index for early infections following living donor liver transplantation

Abstract: Introduction Post-operative infections in patients undergoing living donor liver transplantation (LDLT) are a major cause of morbidity and mortality. This study aims to develop a practical and efficient prognostic index for early identification and possible prediction of post-transplant infections using risk factors identified by multivariate analysis. Material and methods One hundred patients with post-hepatitic cirrhosis, HCV positive, genotype 4, Child B/C or MELD sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There were few studies on the relationship between fever, infection, and other postoperative outcomes in patients who undergo PLOS ONE liver surgery. In a study of risk factors related to infections following living donor liver transplantation, Elkholy et al [55] indicated that fever was an independent predictor of early infectious complication. In our study, the incidence of infection in patients with POF was 24.5%.…”
Section: Plos Onementioning
confidence: 99%
“…There were few studies on the relationship between fever, infection, and other postoperative outcomes in patients who undergo PLOS ONE liver surgery. In a study of risk factors related to infections following living donor liver transplantation, Elkholy et al [55] indicated that fever was an independent predictor of early infectious complication. In our study, the incidence of infection in patients with POF was 24.5%.…”
Section: Plos Onementioning
confidence: 99%
“…In the septic shock phase of the disease, every hour that treatment is delayed can lead to a 7.6% increase in mortality (Kumar et al, 2006 ). In liver transplantation, this phenomenon is not different in the general population, and an early infection due to surgical complications, such as bleeding, bile leak, or rejection, may trigger infections and sepsis with severe consequences in recipients (Kumar et al, 2006 ; Elkholy et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have applied artificial intelligence (AI) and machine learning to identify patients at risk for sepsis earlier, thereby potentially reducing mortality and morbidity (Kumar et al, 2006 ; Nemati et al, 2018 ; Elkholy et al, 2019 ). These methods have typically used an array of clinical and laboratory variables in the electronic medical record (EMR) to predict the risk of sepsis.…”
Section: Introductionmentioning
confidence: 99%